Contributing Management Factors to Performance Management Effectiveness - Roya Anvari; Mariam Janjaria (Journal of Business & Management, 2023)
Effective organizations work like a well-designed and well-oiled industrial machine. Each department is designed and integrated with the whole organization to successfully achieve the results that the organization has planned to achieve and to waste as little time and resources as possible. Organizational effectiveness is a new way to measure and guide organizations to achieve their goals. The study aims to investigate the impact of management factors on performance management effectiveness among managers of information technology. Using data gathered from 151 employees in IT SMEs in Wuhan-China who participated in the survey the present results indicate that there is a significant positive relationship linking management factors and the performance management effectiveness.